New Benchmarks on Protocol Amendment Practices, Trends and their Impact on Clinical Trial Performance. - Getz, Kenneth; Smith, Zachary; Botto, Emily; Murphy, Elisabeth; Dauchy, Arnaud (Therapeutic Innovation & Regulatory Science, 2024)
The Tufts Center for the Study of Drug Development (Tufts CSDD) conducted a follow-up study in 2022 to assess trends in protocol amendment experiences and the impact amendments have had on clinical trial performance, particularly during the COVID-19 pandemic. Sixteen pharmaceutical companies and contract research organizations provided data on 950 protocols and 2188 amendments. The results show that, since 2015, the prevalence of protocols with at least one amendment in phases I–IV has increased substantially (from 57 to 76%) and the mean number of amendments per protocol has increased 60% to 3.3, up from 2.1. Phase I and III protocols saw the highest increases in the mean number of amendments implemented per protocol. A much higher percentage of amendments—77%—were deemed unavoidable with regulatory agency requests and changes to the study strategy as the top reasons cited for amending a protocol. The total average duration to implement an amendment has nearly tripled during the past decade. The time from identifying the need-to-amend to last oversight approval now takes an average of 260 days and the mean duration during which investigative sites operate with different versions of the clinical trial protocol spans 215 days. Protocols that implemented at least one amendment were more effective at increasing patient screening volume and reducing the actual number of patients enrolled relative to plan. Lastly, the prevalence of protocols with at least one amendment and mean number of amendments was significantly higher for protocols conducted during the pandemic.